2022
DOI: 10.3390/app12147245
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Influence of Loading Frequency on the Dynamic Response of Concrete Sleepers

Abstract: The load generated during train operation is transmitted to sleepers through rails, and then from sleepers to trackbeds. As one of the important components of the track structure, sleepers are very important to the service-life and safety of railways. The running speed of the train will produce different load frequencies on the rails. To explore the response of sleepers under cyclical train loads, this research used the discrete element method to simulate rails and sleepers, and realizes the loading of sleeper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 10 publications
1
1
0
Order By: Relevance
“…Furthermore, it was mostly observed an uptrend tendency in the low frequencies range for both viscoelastic parameters, which is in agreement with previous studies that have found an increase in the stiffness of concrete as the frequency decreases (Chen et al, 2022;Medeiros et al, 2015). However, there were divergent values, it should be noted that there was an exception for M2 AVCM, with a downtrend in low-frequencies and some values at 25 Hz, which could potentially be attributed to dynamic effects, labeled as outliers in Fig.…”
Section: Splitting Tensile Strength Results Mortars Formulationssupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, it was mostly observed an uptrend tendency in the low frequencies range for both viscoelastic parameters, which is in agreement with previous studies that have found an increase in the stiffness of concrete as the frequency decreases (Chen et al, 2022;Medeiros et al, 2015). However, there were divergent values, it should be noted that there was an exception for M2 AVCM, with a downtrend in low-frequencies and some values at 25 Hz, which could potentially be attributed to dynamic effects, labeled as outliers in Fig.…”
Section: Splitting Tensile Strength Results Mortars Formulationssupporting
confidence: 92%
“…The behavior of increasing complex modulus with frequency up to 5-10 Hz, followed by a plateau, is resported as usual for viscoelastic materials, usually explained by the microstructure alignment, where further changes in frequency do not affect the modulus signi cantly, which literature can provide insight in similar aspects (Chen et al, 2022;Medeiros et al, 2015;Sanahuja et al, 2007). This is typically attributed to the increased stiffness of the material as the microstructure becomes more ordered at higher frequencies.…”
Section: Splitting Tensile Strength Results Mortars Formulationsmentioning
confidence: 79%